COMPENSATION AND WORKLOAD ANALYSIS FOR EMPLOYEE JOB SATISFACTION - Redy Adhi Saputra; Aulia Umar Hatifah (Jurnal Intelek Insan Cendikia, 2026)
This study is a quantitative research using SPSS 26.0 as a tool for data processing with the saturated sample or census technique used in this study. The results of this study show that compensation (X1) partially has a positive and significant effect on employee job satisfaction (Y), as evidenced by the multiple linear regression test value of (b1) 1.656 and the t-value   calculated > t table is 11.426 > 2.022691 and the significance value is 0.00 < 0.05. Meanwhile, the workload variable (X2) showed a negative and insignificant effect on employee job satisfaction (Y), which can be proven by a multiple linear regression test value of (B2) -0.71 and a t-value calculated < t table which was -0.612 < 2.022691 and a significance value of 0.544 > 0.05. Compensation (X1) and workload (X2) simultaneously have a significant effect on employee job satisfaction (Y), as evidenced by the calculated f value of 134,893 > f table 3.23 and the significance value of 0.000 < 0.05.